2016
DOI: 10.21890/ijres.98946
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review: The Effect of Implementing Technology in a High School Mathematics Classroom

Abstract: This study is a literature review to investigate the effects of implementing technology into a high school mathematics classroom. Mathematics has a hierarchical structure in learning and it is essential that students get a firm understanding of mathematics early in education. Some students that miss beginning concepts may continue to struggle with mathematical computation and concepts throughout the educational experience. One learning strategy that can be implemented throughout the curriculum that can help st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
4
22
0
Order By: Relevance
“…Consequently, these findings support not only Wu et al's (2016) and Zimmerman et al's (2016) claims that beacons can enhance student learning but also Murphy's (2016) claims that educational technology generally can enhance pupil engagement, motivation, collaboration, teacher-student interaction and depth of learning and understanding in the classroom. Furthermore, these findings suggest that beacons enable low ability students to learn as productively as higher ability students in the same lesson.…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, these findings support not only Wu et al's (2016) and Zimmerman et al's (2016) claims that beacons can enhance student learning but also Murphy's (2016) claims that educational technology generally can enhance pupil engagement, motivation, collaboration, teacher-student interaction and depth of learning and understanding in the classroom. Furthermore, these findings suggest that beacons enable low ability students to learn as productively as higher ability students in the same lesson.…”
Section: Discussionsupporting
confidence: 77%
“…In classroom settings, this opens up possibilities to record learner actions and interactions from unique angles (Hummel 2015). iPads are multi-purpose tablet devices, which can serve many educational purposes, such as a platform for educative games and simulations (Murphy 2016). Although the use of tablet devices such as iPads is becoming increasingly common in classrooms, their uses for capturing teacher-student interactions through its video functionality are not well documented.…”
Section: The Value Of Video Feedbackmentioning
confidence: 99%
“…Mathematics is a course which has a linear content organization, sequential and continual learning (Murphy, 2016). Students need to learn previous concepts to get a firm and permanent understanding of mathematics; otherwise, they may struggle with mathematical computations and concepts throughout their mathematical courses.…”
Section: Introductionmentioning
confidence: 99%
“…Students need to learn previous concepts to get a firm and permanent understanding of mathematics; otherwise, they may struggle with mathematical computations and concepts throughout their mathematical courses. However, the results of many studies revealed that students struggle while learning mathematics (Murphy, 2016). It was reported by The National Assessment of Educational Progress report that less than 20% of high school seniors demonstrated a thorough understanding of the mathematical concepts in 2000 and in 2013 approximately 26% of high school seniors showed strong knowledge accuracy of the mathematical concepts which was expressed by the United States Department of Education (Murphy, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation